Magnetic OB[A] Stars with TESS: probing their Evolutionary and Rotational properties (MOBSTER) – I. First-light observations of known magnetic B and A stars. Issue 1 (30th April 2019) - David-Uraz, A; Neiner, C; Sikora, J; Bowman, D M; Petit, V; Chowdhury, S; Handler, G; Pergeorelis, M; Cantiello, M; Cohen, D H; Erba, C; Keszthelyi, Z; et al.
Abstract: In this paper we introduce the MOBSTER collaboration and lay out its scientific goals. We present first results based on the analysis of 19 previously known magnetic O, B, and A stars observed in 2-min cadence in sectors 1 and 2 of the Transiting Exoplanet Survey Satellite ( TESS ) mission. We derive precise rotational periods from the newly obtained light curves and compare them to previously published values. We also discuss the overall photometric phenomenology of the known magnetic massive and intermediate-mass stars and propose an observational strategy to augment this population by taking advantage of the high-quality observations produced by TESS .